SH2B3, Transcribed by STAT1, Promotes Glioblastoma Progression Through Transducing IL-6/gp130 Signaling to Activate STAT3 Signaling - Cai, Shan; Lu, Jian-xiang; Wang, Yan-pei; Shi, Chao-jia; Yuan, Tian; Wang, Xiang-peng (Frontiers in Cell and Developmental Biology, 2021)
Abstract Glioblastoma (GBM) is the most common and aggressive brain tumor in adults. Activation of STAT3 commonly occurs in GBM and promotes GBM progression. In this study, we reported that SH2B adaptor protein 3 (SH2B3) is highly expressed in GBM and GBM stem cells and its high expression predicts worse survival of GBM patients. Targeting SH2B3 expression dramatically impairs GBM cell proliferation, migration and GSCs self-renewal in vitro and xenograft tumors growth in vivo. Moreover, we found that STAT1 directly binds to the promoter of SH2B3 and activates its expression in transcriptional level. In addition, SH2B3 facilitates GBM progression via activating STAT3 signaling. Together, our work uncovers a key function for SH2B3 and provides insight into new prognosis marker and therapeutic target in GBM.